Enhancing Learner Motivation with Digital Tools: The Impact of AI and Gamification on Language Learning Engagement - Sugeng Irianto; Linda Kunda; Siswandi Siswandi (International Journal of Language and Ubiquitous Learning, 2026)
Background. The integration of digital tools, particularly artificial intelligence (AI) and gamification, has significantly transformed language learning. These technologies offer personalized and interactive learning experiences that have the potential to enhance learner motivation and engagement. However, the impact of AI and gamification on language learning remains underexplored, particularly in terms of how these tools influence learners’ intrinsic and extrinsic motivation to engage with language content. Purpose. This study aims to investigate the impact of AI and gamification on learner motivation in language learning. Specifically, the research explores how these digital tools can enhance learner engagement, foster motivation, and contribute to improved learning outcomes in language education. Method. A mixed-methods approach was used, combining quantitative surveys to measure learner motivation and engagement, with qualitative interviews to gather insights into learners’ experiences with AI-based and gamified language learning tools. The study was conducted with 150 participants from diverse backgrounds who used language learning apps incorporating AI and gamification features. Results. The findings show that both AI and gamification significantly increased learner motivation and engagement. Learners reported a higher sense of achievement and enjoyment, with AI providing personalized learning paths and gamification offering rewarding experiences that encouraged continued practice. Conclusion. AI and gamification are effective tools for enhancing learner motivation in language learning. These technologies foster greater engagement and create a more dynamic and enjoyable learning environment, offering valuable tools for future language education strategies.